Identification of pseudouridine methyltransferase in Escherichia coli - Ero, Rya (Cold Spring Harbor Laboratory Press, 2008)

(untitled)
In ribosomal RNA, modified nucleosides are found in functionally important regions, but their function is obscure. Stem–loop 69 of Escherichia coli 23S rRNA contains three modified nucleosides: pseudouridines at positions 1911 and 1917, and N3 methyl-pseudouridine (m(3)Ψ) at position 1915. The gene for pseudouridine methyltransferase was previously not known. We identified E. coli protein YbeA as the methyltransferase methylating Ψ1915 in 23S rRNA. The E. coli ybeA gene deletion strain lacks the N3 methylation at position 1915 of 23S rRNA as revealed by primer extension and nucleoside analysis by HPLC. Methylation at position 1915 is restored in the ybeA deletion strain when recombinant YbeA protein is expressed from a plasmid. In addition, we show that purified YbeA protein is able to methylate pseudouridine in vitro using 70S ribosomes but not 50S subunits from the ybeA deletion strain as substrate. Pseudouridine is the preferred substrate as revealed by the inability of YbeA to methylate uridine at position 1915. This shows that YbeA is acting at the final stage during ribosome assembly, probably during translation initiation. Hereby, we propose to rename the YbeA protein to RlmH according to uniform nomenclature of RNA methyltransferases. RlmH belongs to the SPOUT superfamily of methyltransferases. RlmH was found to be well conserved in bacteria, and the gene is present in plant and in several archaeal genomes. RlmH is the first pseudouridine specific methyltransferase identified so far and is likely to be the only one existing in bacteria, as m(3)Ψ1915 is the only methylated pseudouridine in bacteria described to date.